2012
DOI: 10.1002/jat.2730
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simple assay for the determination of cholinesterase activity in whole blood of laboratory animals

Abstract: Current methods for measuring acetylcholinesterase (AChE) activities in whole blood use butyrylcholinesterase (BChE)‐selective inhibitors. However, the poor selectivity of these inhibitors results in the inhibition of AChE activity to some degree, leading to errors in reported values. The goal of this study was to develop and validate a simple assay for measuring AChE and BChE activities in whole blood from humans as well as experimental animals. Blood was fractionated into plasma and erythrocytes, and choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…On the other hand, the interferent is eliminated in the very low amount of blood samples (corresponds to 0.1 μL of the undiluted blood sample). The total AChE activity in the five human blood samples are also consistent with the AChE activity level in the human blood obtained using other methods (Worek et al, 1999;Sanz et al, 1991;Naik et al, 2013). These results indicate that this technique can reliably detect the total AChE activity assay in submicroliter human blood.…”
Section: Detecting the Total Ache Activity In Human Bloodsupporting
confidence: 84%
“…On the other hand, the interferent is eliminated in the very low amount of blood samples (corresponds to 0.1 μL of the undiluted blood sample). The total AChE activity in the five human blood samples are also consistent with the AChE activity level in the human blood obtained using other methods (Worek et al, 1999;Sanz et al, 1991;Naik et al, 2013). These results indicate that this technique can reliably detect the total AChE activity assay in submicroliter human blood.…”
Section: Detecting the Total Ache Activity In Human Bloodsupporting
confidence: 84%
“…Naik et al reported that more than 90% of plasma ChE activity arises from BChE in Hartley guinea-pig plasma and that this situation is similar in humans. 28) Therefore, any observed plasma ChE inhibitory effects are thought to reflect effects on BChE. Our present findings were consistent with a report by Yamamoto et al, which suggested that the inhibitory effects of distigmine on plasma ChE activities were independent of the dose administered.…”
Section: )supporting
confidence: 93%
“…AChE and BChE activity levels were determined using a modified version of the biochemical assay developed by Naik, Liu, and Saxena () as previously described (Apatzidou et al, ).…”
Section: Methodsmentioning
confidence: 99%